Volatility Spillover from Soybean Oil to Crude Palm Oil Cash and Futures – Empirical Evidence - Kang, ZI Xin (2015)
In the recent year, market players in the global financial market view commodity market as alternative investment area. Therefore, research on volatility spillover in agricultural commodity markets has become an important area for market participants whose marketing decision and production are often affected by risk and uncertainty in commodity market. Previous research has identified relationship in variability and also market precise between the other biofuel, ethanol and energy market, but limited studies has been done to evaluate volatility spillover between soybean oil and crude palm oil. This research employed GJR GRACH and Bivariate BEKK GRACH models to examine the volatility spillover from soybean oil market to crude palm oil market by using daily return from 1st Jan 2004 to 31st December. The empirical result shows that the strong evidence transmission of volatility from soybean oil market to crude palm oil market are similar in magnitude over time. The results also indicate the strong bi-directional causal relationship between crude palm oil futures and spot market after the cross market transmission from soybean oil, suggesting that return volatility in spot market can influence that in the futures market and vice versa. Thus, this result also indicates that new information is reflected in futures and spot markets simultaneously.